2003
DOI: 10.2307/3583342
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of D u Phenotype amongst Rhesus Negative Females in Port Harcourt, Nigeria

Abstract: The prevalence of D u phenotype was investigated among rhesus negative women of childbearing age (15-45 years) in Port Harcourt, Nigeria, over a period of 17 months. A total of 1,108 women were randomly sampled, out of which 1,003 (90.5%) were rhesus positive and 105 (9.5%) rhesus negative. Only one (0.95%) of the Rh-negative women was D u positive while 104 (99.05%) were D u negative (true rhesus negatives). The results show that the incidence of D u phenotype in Nigeria may not be uniform -it is high among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…The finding of 7.75% prevalence of Rh-negative among donors in this study (Fig 1A) is in keeping with available records of low prevalence of Rh-negative in other African countries. Among Kenyans 3.9% has been reported and 1-6% among Nigerians (Nwauche et al, 2003). The low incidence of Rh-negativity contrasts markedly with high figures obtained elsewhere, for example, about 15% -17% among Europeans (Race and Sanger, 1975) and 15% in the USA population (Mollison et al, 1997).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The finding of 7.75% prevalence of Rh-negative among donors in this study (Fig 1A) is in keeping with available records of low prevalence of Rh-negative in other African countries. Among Kenyans 3.9% has been reported and 1-6% among Nigerians (Nwauche et al, 2003). The low incidence of Rh-negativity contrasts markedly with high figures obtained elsewhere, for example, about 15% -17% among Europeans (Race and Sanger, 1975) and 15% in the USA population (Mollison et al, 1997).…”
Section: Discussionmentioning
confidence: 89%
“…The frequency of the weak D phenotype in whites is approximately 0.2% to 1% (Flegel et al, 2000;Wagner et al, 2000), up to 10% in Africans (Cheesbrough, 2000), 7.5% among the Yoruba of South-Western Nigeria, 0.75% in Kenya (Lyko et al, 1992), 0.6% in the United Kingdom (Nwauche et al, 2003) and approximately 0.23% in USA (Mollison et al, 1997). Nwauche et al, (2003) found 0.95% among adult females in Port Harcourt, Nigeria. These varied results from Nigeria depicted heterogeneity in the prevalence of weak D, even among somewhat homogenous entities.…”
Section: Introductionmentioning
confidence: 99%
“…Among Nigerians 1-6% has been reported and 3.9% among Kenyans (6) . High figures obtained elsewhere, for example, about 15% -17% among Europeans ( 7.)…”
Section: Discussionmentioning
confidence: 99%
“…[5] Whereas in a study conducted by Dr. Geeta et all the prevalence was slightly on the higher side (0.49%) On the contrary high prevalence of weak D individuals is seen in Africans (10%). [6,7] Among Indians 0.09%-0.189% prevalence has been reported8. According to American Association of Blood Banks (AABB) it is mandatory to detect the weak D/partial D status of the donor but the recipient can be safely considered as RhD negative.…”
Section: Section: Pathology Discussionmentioning
confidence: 99%
“…Weak D is weakly immunogenic and requires detection by antihuman globulin. [6] Partial D antigen lack one or more epitopes on red blood cells8. Thus RBCs having partial D antigen are agglutinated distinctively by some but not all monoclonal anti D reagents.…”
Section: Introductionmentioning
confidence: 99%